Direct inhibition of Keap1–Nrf2 interaction by egg-derived peptides DKK and DDW revealed by molecular docking and fluorescence polarization. Issue 56 (12th July 2017) - Li, Liangyu; Liu, Jingbo; Nie, Shaoping; Ding, Long; Wang, Liying; Liu, Jiyun; Liu, Wenchao; Zhang, Ting
Abstract : DKK and DDW, egg-derived direct inhibitors of the Keap1–Nrf2 interaction, screening by fluorescence polarization assays and cell experiments. Abstract : Egg-derived small peptides have various biological activities, including antioxidant properties. The Keap1–Nrf2 pathway is central to cell resistance to oxidative stress. In this study, we screened an egg-derived short peptide library to identify molecules with a potential to directly inhibit the Keap1–Nrf2 interaction, using molecular docking, fluorescence polarization assay, and a cytotoxicity model. Among the 20 small peptides selected by molecular docking, two tri-peptides, DKK and DDW, could directly inhibit the binding of the Keap1 Kelch domain to the FITC-labelled 9-mer Nrf2 peptide, as evidenced by increased K d in fluorescence polarization experiments. Furthermore, in H2 O2 -treated cells, DKK and DDW promoted survival and upregulated the activity of catalase and superoxide dismutase, key enzymes involved in detoxification of reactive oxygen species. Our findings indicate that small egg-derived peptides DKK and DDW can exert antioxidant effects and protect cells against oxidative stress by directly inhibiting Keap1–Nrf2 interaction.